2006
DOI: 10.1007/s10439-006-9117-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Dynamic Assessment of Three Polymeric Heart Valves Using Particle Image Velocimetry

Abstract: Polymeric heart valves have the potential to reduce thrombogenic complications associated with current mechanical valves and overcome fatigue-related problems experienced by bioprosthetic valves. In this paper we characterize the in vitro velocity and Reynolds Shear Stress (RSS) fields inside and downstream of three different prototype trileaflet polymeric heart valves. The fluid dynamic differences are then correlated with variations in valve design parameters. The three valves differ in leaflet thickness, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 20 publications
7
58
1
Order By: Relevance
“…3), to simulate pulsatile physiological flow and pressure conditions in an in vitro setup. 11,22,[40][41][42] Compliance and resistance elements were adjusted to achieve desired flow and pressure conditions. The cardiac output, ventricular pressure and aortic pressure were measured at 500 Hz using a custom LabView program for 15 cycles, to obtain statistically converged ensemble averaged flow and pressure curves.…”
Section: Valve Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…3), to simulate pulsatile physiological flow and pressure conditions in an in vitro setup. 11,22,[40][41][42] Compliance and resistance elements were adjusted to achieve desired flow and pressure conditions. The cardiac output, ventricular pressure and aortic pressure were measured at 500 Hz using a custom LabView program for 15 cycles, to obtain statistically converged ensemble averaged flow and pressure curves.…”
Section: Valve Modelsmentioning
confidence: 99%
“…11,22,29 The present PIV system consisted of a pair of pulsed Nd:YAG lasers (ESI Inc., Portland, OR; 17 mJ energy, 532 nm wavelength, 9 ns pulse duration) and a combination of spherical and cylindrical lenses to create a laser sheet. The flow was seeded with fluorescent polymethyl methacrylate (PMMA) particles (Dantec Dynamics, Denmark, D = 1-20 lm, labeled with Rhodium-B dye, emission at 580 nm).…”
Section: Particle Image Velocimetry Experimentsmentioning
confidence: 99%
“…The flows also do not likely correspond to significant blood damage conditions due to the very short exposure times. 39,78 Paul et al 53 reported that for exposure times ranging between 25 and 1250 ms, for a minimum shear stress of 300 dyne/cm 2 , the maximum hemolysis, characterized by the hemolysis index (HI), reaches 3.5%. Since the median exposure time calculated from the present PIV measurements is only 3.5 ms, it is unlikely that blood damage is significant for either anatomical junction.…”
Section: Discussionmentioning
confidence: 99%
“…7). 17,26,[45][46][47]64,66,68,76,77,88,91,97,98,103,130,138 However, PIV methods were mainly two dimensional until Bru¨cker introduced Stereo-PIV based on the use of two digital cameras and PIV algorithms to study the flow past artificial heart valves. 21 The testing requirements for performing stereo-PIV for characterizing the flow through mechanical heart valves has been well described by Morbiducci et al 115 Another breakthrough in PIV was the development of defocusing digital particle image velocimetry (D-DPIV).…”
Section: Particle Image Velocimetry Of Heart Valvesmentioning
confidence: 99%